Determination of Organizational and Individual Factors on Teacher Performance and Achievement - Tuha, Panca Tuah; Sukiman, Sukiman; Hamdan, Hamdan; Wargianto, Wargianto; Yani, Ahmad (STIE Tri Bhakti, 2025)
Teacher performance is a strategic component in ensuring the effectiveness of the learning process and the achievement of educational goals. This study aims to examine the influence of organizational culture, communication, discipline, and competence on teacher performance and its impact on teacher achievement. The research was conducted at SMAN 1 Kelapa, Bangka Barat Regency, using a quantitative approach with an associative-causal design. The population consisted of 42 teachers, selected through a census method. Data were collected using a Likert-scale questionnaire and analyzed through multiple and simple linear regression using SPSS version 24.0. The findings reveal that all four independent variables—organizational culture, communication, discipline, and competence—have a simultaneous and significant effect on teacher performance, with an adjusted R² value of 0.701. Each variable also has a significant partial effect, with competence emerging as the most dominant factor. Furthermore, teacher performance has a positive and significant influence on teacher achievement, with an adjusted R² value of 0.586. These results indicate that the improvement of teacher achievement is highly dependent on performance quality, which is shaped by the synergy between organizational and individual factors. The study implies that enhancing teacher achievement requires strengthening inclusive organizational culture, fostering effective communication, reinforcing discipline through professional awareness, and continuously developing teacher competence to support optimal and sustainable performance.